Caracterização de farinhas de feijão crioulo (Phaseolus vulgaris L.) e sua utilização na elaboração de maionese - Alves, Jamila dos Santos (2016)
The objective of this study was to characterize the two landrace common bean flour (in shell and shelled) and then apply one of them in partial replacement of mayonnaise in egg yolk. After obtaining the flour, it was performed performance analysis, chemical composition, pH, color, total phenolic compounds, flavonoid and antioxidant activity in vitro (DPPH and FRAP) and technological functional properties of absorbency for water and oil and emulsifying properties. The results show that the chemical composition of the landrace common bean flour (LCBF) is an important source of protein and fiber. Phenolic compounds were higher than in the LCBF in shell, and to cultivar Manteigão showed the highest reducing power by FRAP method, higher content of phenolic compounds and antioxidant capacity of the Carioca. The LCBF in shell from two cultivars showed better water absorption capacity and capacity oil absorption, indicating that can be used in food systems such as soups, bakeries, meat products which require high absorption of water and fat. As the results preliminary, the LCBF in shell Carioca was chosen flour for the preparation of mayonnaise. Mayonnaise were developed four formulations: T1 (Default) 100% egg yolk (EY); T2 75% EY and 25% LCBF; T3 50% EY and 50% LCBF; T4 25% EY and 75% LCBF. Analyses of chemical composition were held, calories, cholesterol, microbiological analysis, microscopy, rheology study, pH, Aw, color, stability and sensory analysis. The partial replacement of the EY by LCBF improved nutritional characteristics of mayonnaise, increased protein content and decreased the content of lipids and cholesterol. All samples showed non-Newtonian shear thinning behavior, yet, all samples showed the hysteresis phenomenon. The values of n were increased and K showed a decrease over storage. There was a decrease in apparent viscosity values for all the mayonnaise samples. The pH and Aw values decreased during storage, as well as the values of L * indicates a darkening of the product over the 30 days of storage. For the stability of the emulsion, treatment with a higher proportion of LCBF was less stable during storage. In sensory evaluation, the tasters did not notice difference between treatments for the color, odor, and overall appearance. In purchase intent test, T1, T2 and T3 showed the highest response rates for the score "Probably buy." The replacement of 50% of egg yolk by 50% landrace common bean flour (T3) showed up a good alternative for the production of mayonnaise, as obtained good acceptability, showed an increase in protein content, total dietary fiber and decrease the included lipids and cholesterol content of the product.